PENERAPAN KONSEP PENGELOLAAN SAMPAH RUMAH TANGGA DENGAN METODE 5R (REDUCE, REUSE, RECYCLE, REPLACE, AND REPLANT) BERBASIS MASYARAKAT DI WILAYAH KEBRAON KOTA SURABAYA - Firra Rosariawari; Alfredo Paelongan (EnviroUS, 2022)
Garbage management with the 5R concept (Reduce, Reuse, Recycle, Replace, and Replant) is one method that was considered complex in dealing with garbage problems in the planning area. The 5R method that involving community participation will be able to reduce the rate of garbage generation that occurs in the research area. Analysis of the data using the correlation analysis method to show a fairly good correlation between the participation of the community in managing garbage and reducing the garbage produced. Research data shows that with the 5R method, the community can reduce garbage as much as 40.83% of the garbage generated by the community, in other words, community participation in implementing the 5R concept can answer the problem of the large number of household garbage generation which is the main source of garbage generation in the Kebraon area, Surabaya city.